2020
DOI: 10.1111/emre.12407
|View full text |Cite
|
Sign up to set email alerts
|

Job Overload, Organizational Commitment, and Motivation as Antecedents of Cyberloafing: Evidence from Employee Monitoring Software

Abstract: The study aims to investigate how organization-related factors, such as job overload, organizational commitment, and motivation, affect the level of cyberloafing. While research on cyberloafing has been blooming recently, most of the studies are based on self-reports. Thus the validity of obtained results is threatened by the possibility of deliberate response distortion resulting in the underreporting of cyberloafing. We address this issue by using a unique data-set collected by the organization-wide computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 70 publications
(92 reference statements)
0
21
0
2
Order By: Relevance
“…5.3.1.3 Socio-demographic differences. The review suggests that most scholars have utilized socio-demographic indicators, like education (Agarwal and Avey, 2020), marital status (Wu et al, 2020), organizational tenure (Cheng et al, 2020), age and gender (Hensel and Kacprzak, 2020;Zoghbi-Manrique-de-Lara et al, 2019), as control variables. However, few studies have also found socio-demographic-related differences in cyberloafing (Sheikh et al, 2015), the results have been inconsistent.…”
Section: Antecedents and Stakeholdersmentioning
confidence: 99%
See 1 more Smart Citation
“…5.3.1.3 Socio-demographic differences. The review suggests that most scholars have utilized socio-demographic indicators, like education (Agarwal and Avey, 2020), marital status (Wu et al, 2020), organizational tenure (Cheng et al, 2020), age and gender (Hensel and Kacprzak, 2020;Zoghbi-Manrique-de-Lara et al, 2019), as control variables. However, few studies have also found socio-demographic-related differences in cyberloafing (Sheikh et al, 2015), the results have been inconsistent.…”
Section: Antecedents and Stakeholdersmentioning
confidence: 99%
“…According to Vitak et al (2011), there is a differential effect of antecedents like socio-demographic factors, Internet utility and routine Internet use on the jobs that require repetitive actions visa-vis creativity. Studies have determined that cyberloafing is predicted by an employee's organizational commitment (Hensel and Kacprzak, 2020), job embeddedness (Karimi Mazidi et al, 2020;Saghih and Nosrati, 2020) and identification with the job characteristics and stressors (Zhou et al, 2021), such as role conflict (Henle and Blanchard, 2008), job (Hensel and Kacprzak, 2020) or role overload (Varghese and Barber, 2017) and underload (Pindek et al, 2018). For instance, Elrehail et al (2021) found job demands, as well as stress, increased cyberloafing, while job resources and work engagement decreased this behavior.…”
Section: Peer Co-workermentioning
confidence: 99%
“…Although some researchers have used employee motivation to measure job performance (Pindek et al, 2019), knowledge transfer (Cruz et al, 2009), and organizational performance (Rehman et al, 2019a), less attention has been paid to its effect on cyberloafing behavior. Hensel & Kacprzak (2020) asserted that employee motivation has no influence on cyberloafing, indicating the need to study this relationship further to account for the variation in findings.…”
Section: Employees' Motivation Cyberloafing Behaviormentioning
confidence: 99%
“…Rezultati naše analize pri preverjanju povezave spola zaposlenih in spletnega postopanja se ujemajo z ugotovitvami drugih raziskav (Dejak et al, 2020, Ahmad in Omar, 2017Baturay in Toker, 2015;Hensel in Kacprzak, 2020;Sheikh et al, 2015). Ugotovili smo, da so razlike med aritmetičnima sredinama pri moških in ženskah statistično značilne (t = 2,697; p = ,028); povprečna vrednost spletnega postopanja je višja pri moških.…”
Section: Razpravaunclassified